Analisis Model Pembelajaran Kooperatif Tipe Make A Match Sebagai Upaya Meningkatkan Pemahaman Konsep Surat Niaga - Fita Indah Sry Permata; Jaka Nugraha (Jurnal Pendidikan Administrasi Perkantoran (JPAP), 2020)
This article describes a study of cooperative learning models with the type of make a match that leads to the concept of student understanding, especially in the matter of commercial letters. Trading letters are basic competencies in correspondence subjects. Where in the material about this commercial letter, there is considerable material ranging from understanding, characteristics, functions, and types of commercial letters to the procedure for making letters. But in reality, one of the main problems in learning commercial letters is the low understanding of the concept of commercial letters; this is because teachers on subjects have not been able to apply learning models that are in accordance with the material that has been delivered so that students feel bored and sleepy when receiving monotonous material. With this phenomenon, the researcher has an alternative in dealing with these problems by using a make a match type of cooperative learning model in which this model students can learn and play to understand the concepts of the material delivered by the teacher, games made by matching question cards and answer cards so that students are assigned looking for partners in turn. This article discusses based on the scope starting from the understanding of the learning model, the function of the learning model, the characteristics of the learning model, then discusses the understanding of the cooperative learning model and the objectives of the cooperative learning model further describing the make a match starting from the understanding, objectives, advantages, and disadvantages along with the syntax of the make a match learning model and the last result and discussion of the analysis cooperative learning models with the type of make a match as an effort to increase understanding of  the concept of commercial letters.